Isokinetic muscle function, dynamic balance, and injury risk in dominant and non-dominant lower extremities of adolescent taekwondo athletes - Dong, M.; Kim, B.; Lee, J.; Choi, Y.; Shi, P.; Zhang, G. (Frontiers in Sports and Active Living, 2025)
Background: Adolescent Taekwondo athletes are exposed to distinct musculoskeletal demands, where imbalances in muscle function and deficiencies in dynamic balance may increase their risk of injury.